Comparative effectiveness of phlegm-heat clearing Chinese medicine injections for AECOPD: A systematic review and network meta-analysis. (28th June 2022) - Chen, Xueyin; Kang, Fuqin; Lai, Jiaqi; Deng, Xueyi; Guo, Xinfeng; Liu, Shaonan
Abstract: Ethnopharmacological relevance: Qingkailing (QKL), Reduning (RDN), Xiyanping (XYP), Tanreqing (TRQ) and Yuxingcao (YXC) injections are all phlegm-heat clearing Chinese medicine (CM) injections composed of the extract from traditional CM materials. Evidence from clinical studies and animal experiments indicates that the above CM injections are effective supplementary therapy for acute exacerbation chronic obstructive pulmonary disease (AECOPD), and clinicians are faced with a difficult choice on the optimal phlegm-heat clearing CM injection for AECOPD. Aim of the study: This systematic review and Bayesian network meta-analysis aimed to evaluate the comparative effectiveness of five commonly used phlegm-heat clearing CM injections for COPD. Materials and methods: A pairwise and network meta-analyses were performed to assess the effectiveness of QKL, RDN, TRQ, XYP and YXC on AECOPD. Randomized controlled trials (RCTs) were identified by searching English and Chinese databases. The primary outcome was lung function (forced expiration volume [FEV1] and forced vital capacity [FVC]), blood gas analysis index was secondary outcome measure. Winbugs and Stata 15.0 software were used for data analysis. Results: A total of 57 RCTs were included. The pairwise analyses showed that each of the injections combined with routine treatment were superior to routine treatment alone [FEV1: QKL, MD 0.20, 95% CI (0.06, 0.35); RDN, MD 0.24, 95% CI (0.08, 0.40); TRQ, MD 0.24, 95% CI (0.19, 0.29); XYP, MD 0.26, 95% CI (0.20, 0.32); YXC MD 0.73, 95% CI (0.06, 1.41)]. The network meta-analysis provided the following rank of lung function improvement: FEV1: YXC > TRQ > XYP > RDN > QKL; FVC: YXC > TRQ > QKL > RDN > XYP. RDN and YXC ranked highest in blood gas analysis index. RDN was the highest ranked injection for effectiveness, followed by QKL, TRQ, XYP, then YXC. Most of the injections appeared safe, with severe adverse events rarely reported. Conclusion: This study suggests that YXC and TRQ are the most effective therapies in treating AECOPD patients. RDN and YXC are more effective in the alleviation of clinical symptoms. Given that the safety of YXC is controversial, TRQ and RDN may be preferable as phlegm-heat clearing CM injections in the adjuvant treatment of AECOPD. Graphical abstract: Image 1 Highlights: ● This study is the first network meta-analysis that examines phlegm-heat clearing injections related to the treatment of acute exacerbation chronic obstructive pulmonary disease (AECOPD) patients. ● The surface under the cumulative ranking curves was used to estimate the hierarchy of the different injections. ● Phlegm-heat clearing Chinese medicine injections can improve the effective rate, lung function, and arterial blood gas in treating AECOPD. ● Tanreqing injection and Reduning injection were more recommended for treating AECOPD as complementary and alternative therapy.